2010
DOI: 10.3390/s101009493
|View full text |Cite
|
Sign up to set email alerts
|

A Distance-Based Energy Aware Routing Algorithm for Wireless Sensor Networks

Abstract: Energy efficiency and balancing is one of the primary challenges for wireless sensor networks (WSNs) since the tiny sensor nodes cannot be easily recharged once they are deployed. Up to now, many energy efficient routing algorithms or protocols have been proposed with techniques like clustering, data aggregation and location tracking etc. However, many of them aim to minimize parameters like total energy consumption, latency etc., which cause hotspot nodes and partitioned network due to the overuse of certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(41 citation statements)
references
References 21 publications
0
41
0
Order By: Relevance
“…The proposed path deals with variable topology that was, in fact in the light of the path quality with the use of path differences and link disconnectivity enhancement. Wang et al 26 suggested distance-based energy aware routing (DEAR) protocol which not only assured energy efficiency but also ensured efficient load balancing. Diverse traffic and energy models have been utilized as premise to this protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The proposed path deals with variable topology that was, in fact in the light of the path quality with the use of path differences and link disconnectivity enhancement. Wang et al 26 suggested distance-based energy aware routing (DEAR) protocol which not only assured energy efficiency but also ensured efficient load balancing. Diverse traffic and energy models have been utilized as premise to this protocol.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The whole process is completed by two steps: the tool chooses the appropriate subset from the data set as the training set to gain training model firstly, and then uses the model to run the testing set to get the recommendation for the target user. This algorithm is simple to implement and it can avoid the disadvantages of data sparseness and cold boot, but its recommendation for the target user may be useless [15,16].…”
Section: Machine Learning Recommendation Algorithmmentioning
confidence: 99%
“…The work proposed by Jin Wang et al [11] suggests a distance-based energy aware routing algorithm to ensure energy efficiency and maximize network lifetime. Two metrics have been used in this algorithm, individual distance and residual energy.…”
Section: Related Workmentioning
confidence: 99%